Digital ledger technology: A factor analysis of financial data management practices in the age of blockchain in Jordan - Mohammad, Anber Abraheem Shlash; Mohammad, Suleiman Ibrahim Shelash; Al-Daoud, Khaleel Ibrahim; Vasudevan, Asokan; Hunitie, Mohammad Faleh Ahmmad (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the impact of blockchain technology on financial data management practices in Jordanian organizations. The research aims to understand how blockchain influences key aspects such as efficiency, security, transparency, auditability, data integrity, fraud reduction, and cost efficiency. A quantitative approach was employed, using Principal Component Analysis (PCA) and Factor Analysis to extract and analyze significant components from the dataset. The PCA results revealed that the first seven components explained approximately 89.63% of the total variance, with the strongest loadings on efficiency (14.56%), security (13.59%), and transparency (13.10%). Factor analysis further reinforced these findings, highlighting the positive relationship between blockchain adoption and improvements in these key areas. Despite the benefits, implementation challenges emerged as significant moderating factors, impacting the extent to which organizations can fully leverage blockchain technology. The study concludes that blockchain has the potential to transform financial data management, particularly in improving efficiency, security, and transparency. However, organizations must address implementation challenges to fully realize these benefits.